PENGARUH JUMLAH SUDU TERHADAP DAYA DAN EFISIENSI TURBIN AIR CROSSFLOW UNTUK PEMBANGKIT LISTRIK TENAGA PICO HIDRO - Kukuh Lintang Pradisha; Husin Bugis; Danar Susilo Wijayanto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2023)
Indonesia has the potential for water energy that can be utilized as a pico-scale hydroelectric power plant or PLTPH. Water is a renewable energy (EBT) which has the potential to be developed in Indonesia due to the geographical conditions that have a lot of water in mountainous areas as well as irrigation for residential areas. Water turbines can convert water energy into electrical energy. One type of turbine that can be utilized is a crossflow water turbine. This study aims to determine the effect of the number of blades with the use of a nozzle on the power and efficiency of the turbine produced by the crossflow water turbine. The study used experimental methods, the data obtained were analyzed using quantitative descriptive analysis techniques. Variations in the number of blades used in the study were blades with a total of 18 blades, 20 blades, and 22 blades, as well as variations in the angle of attack of the nozzle used, namely 20⁰, 25⁰, 30⁰, 35⁰, and 40⁰. The results showed that there was an effect of using the number of blades and nozzle diameter. The power and efficiency of the turbine fluctuate based on the water discharge. The highest data was obtained at a water discharge of 25.33 l/m, namely using a number of 22 blades using a nozzle diameter of 7 mm to produce 9.47 watts of electric power with an efficiency of 58%.